PERSEPSI DAN PERILAKU MASYARAKAT PONTIANAK TIMUR TERHADAP PERBANKAN SYARIAH - Yulia Yulia (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
This research was qualitative descriptive through deep interview with people of KecamatanPontianak timur. The data sources were taken by means of cluster sampling. According to data analysis, 88.33% informants stated that there must be a fatwa of MUI which declares that interest of bank is haram. The perceptions of people of Kecamatan Pontianak Timur regarding Islamic banking were grouped into three groups: first was a group of people that had positive perception. Second was a group of people who possessed negative perception. Third was a group of people who were doubtful. Based on people’s perception of market system of Islamic banking, there were 5.88% people acknowledged the system. Meanwhile, according to rent expense system of Islamic banking, all informants confessed that they did not recognize it. The attitude of people of Pontianak Timur toward Islamic banking can be categorized into two board groups. First group, 20.58 % were customers of Islamic bank. They stated that they became customers of Islamic bank because 1) they lived near the bank. 2) They were curious about Islamic banking.3) They considered that Islamic banking fit Islamic syari’ah. Second group, 79.42%were not customers of Islamic bank. They stated that were not Islamic bank customers because 1)their salary were paid into conventional bank account. 2) They never performed transaction in Islamic bank before. 3) They considered that the process of transaction was very time consuming. 4) They thought that both of Islamic bank and conventional bank were just the same.